Evaluasi Pemasok Pada Industri Kimia Penjernih Air Dengan Metode AHP Dalam Kerangka Supplier Relationship Management - Angga Widyas Swara; Abby Yazid Bustommy (Operations Excellence: Journal of Applied Industrial Engineering, 2022)
Maintaining the quality of raw materials or materials is a must, so it is necessary to evaluate and select the right supplier to maintain the stability of each chain process. It is impossible to successfully produce low-cost and high-quality products without competent selection and maintenance. This study aims to propose an evaluation model and supplier selection in the water purification chemical industry with Poly Aluminum Chloride (PAC) products within the framework of Supplier Relationship Management (SRM). This research was conducted at a company engaged in the water treatment chemical industry with Poly Aluminum Chloride (PAC) products in powder and liquid form with a production capacity of 19MT/year. PAC is a chemical coagulant used to purify water in wastewater treatment plants and clean water. The method used in this research is the Analytical Hierarchy Process (AHP). The criteria used in this research are Quality, Cost, Delivery, Flexibility, and Responsiveness. Data collection was done by filling out questionnaires to 26 respondents who played a role in making purchasing decisions for raw materials. The results in this study indicate that the Quality Criteria have the largest proportion of weights which if in percent units are 38.9%, discussed by Cost 20.7%, Responsiveness 15.9%, Delivery 12.6%, and the last order is flexibility 11 ,9%. Based on each of these criteria weights, a dashboard is created that functions to provide an assessment to each supplier and provide feedback to suppliers in the form of assessment reports and recommendations given to suppliers.